Investigation of students’ perceptions of out-of-school learning environments through drawing pictures - MERTOĞLU, HATİCE (My University, 2023)
In recent years, out-of-school learning has become more and more important, thus creating new learning environments for students. Out-of-school learning enables students to discover new information both by having fun and by experiencing. The purpose of this research study was to investigate the perceptions of secondary school students about out-of-school learning environments through the pictures they drew. The research design was carried out as an art-based phenomenological approach. The study group of the research consisted of 22 eighth grade students. The data of the research were obtained simultaneously with two open-ended questions for the phenomenological design side and with the pictures drawn by the students for the art-based research side. The data were analyzed by utilizing a content analysis method. Results indicated that students mostly expressed their out-of-school learning environments as courses, home, and internet. When drawing out-of-school learning environments, students drew more “course, study room, internet, television and home” figures. Students stated their favorite learning environments as home, internet, and course. Students stated the reasons for their favorite learning environments as they are more peaceful at home, the first learning begins in the family, they can access everything more easily with the internet, and the course helps the school. It is noteworthy that students do not give examples of museums, science centers and planetariums as learning. According to the results of the research, it was determined that the students generally gave examples from their own environment as an out-of-school environment, and it was determined that they did not experience environments such as museums, planetariums, zoos, or science centers. Since students’ perceptions of out-of-school learning environments were very low, it can be suggested to teachers to plan activities and activities for them to teach in out-of-school learning environments.
Keywords: Out-of-school learning environment; drawing pictures; art-based phenomenological approach; secondary school students